The Effect of Liquidity Risk on the Financial Performance of Commercial Bank Listed on the Indonesian Stock Exchange - Kholis, Muhammad Shofy Muhaiminu; Anugrah, Fatimah Ladiza Nuradhelia; Lestari, Henny Setyo (International Journal of Accounting and Management Research, 2025)
This study aims to examine the variables that affect financial performance in commercial banks listed on the Indonesia Stock Exchange. The method used is secondary data collection from 41 commercial banks over a five-year period (2019–2023), with a total of 205 data that meet the criteria. The data analysis used is the panel data regression method using EViews 9 software. The results of the study obtained that the Current Ratio and Capital Adequacy Ratio do not affect the bank's financial performance, while the Loan to Deposit Ratio and Loan to Asset Ratio have a positive effect on the bank's financial performance. Liquidity Gap Ratio, Non-performing Loans, and Deposits have been shown to have a negative effect on the bank's financial performance. The urgency of this research lies in the critical role of banking in maintaining financial system stability and supporting national economic growth, where weak financial performance and poor risk management can threaten public trust and overall economic resilience. Therefore, the results of this study are expected to be a reference for conventional banks in determining the factors that affect the bank's financial performance.